Studying the Impact of Gamma Radiation on the Electrical Properties of Insulating Oil at High Voltage Equipment (Case Study) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Engineering Sciences Series, 2025)
Since the discovery of radioactive decay of isotopes and the emission of rays from this decay, interest began in investing these rays peacefully. The uses of radiation have developed with industrial and technological development so that they have come to include multiple areas of human activities, as the number of radiation facilities invested commercially in the world exceeds 180 facilities. In this research a sample of mineral insulating oil was irradiated with gamma radiation source Co 60 with a radioactivity of 70 kCi, where the irradiation process was carried out at a dose rate of (8.9 KGray/hour) , under  different doses up to 250 KGray. The studied sample used in high voltage equipment in the Ministry of Electricity in Syria. The value of breakdown voltage of sample was studied in accordance the approved conditions and standards using  (MEGGER OTS 60PB) device, which works on the principle of applying a gradual voltage at a rate of 2-5Kv/sec to the insulating oil within the test cup until the oil insulation collapses, which represents the breakdown voltage value, and the test is repeated automatically more than once, as the breakdown voltage value for the sample it was 36 Kv before irradiation . The results show a decrease in breakdown voltage , the minimum value was 22Kv with dose 250 KGray  . The results were compared with the international reference values ​​(IEC 60156). Simple Linear Regression methodology was used to study the relationship between breakdown voltage and radiation doses, and the mathematical model was obtained and the correlation coefficient was calculated, and its value was 0.9651. In our study, we concluded that the dose 150 KGray is the dose at which the breakdown voltage clearly began to deteriorate, which negatively affects the strength of the studied mineral insulating oil.